DAMPAK REMITAN EKONOMI TERHADAP POSISI SOSIAL BURUH MIGRAN PEREMPUAN DALAM RUMAH TANGGA - Asih Sulistiyo, Putri; Sri Wahyuni, Ekawati (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2012)
The objectives of this study are to analyse the push-pull factor of international migration and the impact of economic re mittance s t o migrant women’ s soc i al posit i on i n t he house hol d. Background of i ts research is feminization of international migrant into line with the phenomenon of economic globalization. The magnitude economic remittances generate by the women migrants pre sumabl y wi ll aff ect women’ s social position in the houshold. Culturally, women in this areas do not have a strong decision making power relative to the men in the household. The women migrant working abroad was mainly driven bThe women migrant working abroad was mainly driven b proverty. The return women migrant are likely to have stroger decision making power in the household be case of their major contribution in the household economy. Keywords: woman migrant, social position, household.